Determination of the sevoflurane sparing effect of methadone in cats - Ferreira, Tatiana H. [UNESP]; Steffey, Eugene P.; Mama, Khursheed R.; Rezende, Marlis L.; Aguiar, Antonio J. A. [UNESP] (Wiley-Blackwell, 2011)
Objective To determine the magnitude and duration of sevoflurane minimum alveolar concentration (MAC) reduction following a single intravenous (IV) dose of methadone in cats.Study design Prospective experimental study.Animals Eight (four females and four males) healthy mixed-breed adult (1-2 years) cats weighing 5.82 +/- 0.42 kg.Methods Anesthesia was induced and maintained with sevoflurane. Intravenous catheters facilitated administration of methadone and lactated Ringer's solution. After baseline MAC determination in triplicate using a tail clamp technique. 0.3 mg kg(-1) of methadone was administered IV. End-tidal sevoflurane concentration (E'SEVO) was reduced and MAC was redetermined. In an effort to determine the duration of MAC reduction, measurements were repeated in a stepwise manner until MAC values returned to baseline. After the last stimulation, the E'SEVO was increased to 1.2 individual MAC for 15 minutes, then sevoflurane was discontinued and cats were allowed to recover from anesthesia.Results Baseline sevoflurane MAC was 3.18 +/- 0.06%. When compared with baseline the sevoflurane MAC after methadone administration was significantly reduced by 25, 15 and 7% at 26, 76 and 122 minutes, respectively. The final MAC value (3.09 +/- 0.07%) determined 156 minutes after methadone administration was not significantly different from baseline.Conclusions and clinical relevance Intravenous methadone (0.3 mg kg(-1)) significantly decreased MAC of sevoflurane in cats but the effect was short-lived.
Keywords: cat; methadone; minimum alveolar concentration; sevoflurane